Adverse drug reactions and associated factors in multidrug-resistant tuberculosis: A retrospective review of patient medical records at Mbarara Regional Referral Hospital, Uganda - Kushemererwa, Oliver; Nuwagira, Edwin; Kiptoo, Joshua; Yadesa, Tadele Mekuriya (SAGE Open Medicine, 2023)
Objectives: The World Health Organization pragmatic guidelines recommend shorter duration drug regimens with newer, more efficacious agents for treatment of multidrug-resistant tuberculosis. However, adverse drug reactions associated with the use of newer, second-line agents may pose a major barrier to adequate management of multidrug-resistant tuberculosis. We therefore sought to investigate the prevalence and factors associated with adverse drug reactions among patients with multidrug-resistant tuberculosis. Methods: We retrospectively reviewed patient medical records at the tuberculosis treatment unit of Mbarara Regional Referral Hospital, between January 2013 and December 2020. Medical records were included in the study, if the patients were aged ⩾18 years, tested sputum positive for multidrug-resistant tuberculosis, with adequate pharmacovigilance data documented. We assessed all documented health-related patient complaints, deranged laboratory values, and clinician suspected adverse drug reactions for scientific/clinical plausibility. Adverse drug reactions were confirmed using published and manufacturer drug references materials. A multidisciplinary clinician team was involved to decide whether to exclude or include a suspected adverse drug reaction. Results: About 6 in 10 (67.4%; 120/178) patients experienced at least one adverse drug reactions during treatment, of which 18.3%, 14.6%, and 11.4% of adverse drug reactions affected the endocrine/metabolic, otic, and musculoskeletal body systems, respectively. Majority of the adverse drug reactions were probable and had a moderate severity. There was an upward trend in adverse drug reaction incidence between 2015 and 2019. Adverse drug reaction occurrence was associated with previous adverse drug reaction history (adjusted odds ratio = 2.85 (1.08, 7.53 at 95% confidence interval)); however, patients who were underweight (adjusted odds ratio = 0.34 (0.16, 0.69 at 95% confidence interval)) and those treated with bedaquiline-based drug regimens (adjusted odds ratio = 0.2 (0.07, 0.59 at 95% confidence interval)) were less likely to experience an adverse drug reaction. Conclusion: Majority of patients with multidrug-resistant tuberculosis experience at least adverse drug reaction during the course of treatment. The newer standard shorter duration drug regimens (9–12 months) may be associated with intolerable adverse drug reactions that hamper effective management of multidrug-resistant tuberculosis. There is need for more studies to assess the clinical adverse drug reaction burden associated with the implementation of shorter duration regimens.
Keywords: Adverse drug reactions; Multidrug-resistant tuberculosis; Uganda